PreSERVE-AMI: A Randomized, Double-Blind, Placebo-Controlled Clinical Trial of Intracoronary Administration of Autologous CD34+ Cells in Patients With Left Ventricular Dysfunction Post STEMI - Quyyumi, Arshed A.; Vasquez, Alejandro; Kereiakes, Dean J.; Klapholz, Marc; Schaer, Gary L.; Abdel-Latif, Ahmed; Frohwein, Stephen; Henry, Timothy D.; Schatz, Richard A.; Dib, Nabil; Toma, Catalin; Davidson, Charles J.; et al. (Circulation research, 2017)
RATIONALE:Despite direct immediate intervention and therapy, ST-segment–elevation myocardial infarction (STEMI) victims remain at risk for infarct expansion, heart failure, reinfarction, repeat revascularization, and death. OBJECTIVE:To evaluate the safety and bioactivity of autologous CD34+ cell (CLBS10) intracoronary infusion in patients with left ventricular dysfunction post STEMI. METHODS AND RESULTS:Patients who underwent successful stenting for STEMI and had left ventricular dysfunction (ejection fraction≤48%) ≥4 days poststent were eligible for enrollment. Subjects (N=161) underwent mini bone marrow harvest and were randomized 1:1 to receive (1) autologous CD34+ cells (minimum 10 mol/L±20% cells; N=78) or (2) diluent alone (N=83), via intracoronary infusion. The primary safety end point was adverse events, serious adverse events, and major adverse cardiac event. The primary efficacy end point was change in resting myocardial perfusion over 6 months. No differences in myocardial perfusion or adverse events were observed between the control and treatment groups, although increased perfusion was observed within each group from baseline to 6 months (P<0.001). In secondary analyses, when adjusted for time of ischemia, a consistently favorable cell dose–dependent effect was observed in the change in left ventricular ejection fraction and infarct size, and the duration of time subjects was alive and out of hospital (P=0.05). At 1 year, 3.6% (N=3) and 0% deaths were observed in the control and treatment group, respectively. CONCLUSIONS:This PreSERVE-AMI (Phase 2, randomized, double-blind, placebo-controlled trial) represents the largest study of cell-based therapy for STEMI completed in the United States and provides evidence supporting safety and potential efficacy in patients with left ventricular dysfunction post STEMI who are at risk for death and major morbidity. CLINICAL TRIAL REGISTRATION:URLhttp://www.clinicaltrials.gov. Unique identifierNCT01495364.